Investigation of the barrier options pricing models - Palivonaitė, Rita; Valakevičius, Eimutis (Lietuvos matematikos rinkinys, 2009)
In the article three methods of barrier option pricing are analysed and compared: Black–Scholes, trinomial ant adaptive mesh algorithm. Investigation with Lithuanian firm’s stock showed, that to get better results it is offered to adapt higer resolution mesh on critical regions of trinomial tree.
Keywords: barrier option; trinomial tree; adaptive mesh algorithm